Energetic materials : advanced processing technologies for next-generation materials - Groven, Lori J.; Kalyon, Dilhan M.; Mezger, Mark J.; Pantoya, Michelle; Tindle, Kay J.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2017)
This book will take an in-depth look at the technologies, processes, and capabilities to develop and produce "next generation" energetic materials for both commercial and defense applications, including military, mining operations, oil production and well perforation, and construction demolition. It will serve to highlight the critical technologies, latest developments, and the current capability gaps that serve as barriers to military fielding or transition to the commercial marketplace. It will also explain how the processing technologies can be spun out for use in other non-energetics related industries.
part 1 Critical Science and Technologies in the Life Cycle of Energetic Materials -- chapter 1 Synthetic Methods for High-Energy Organofluorine Compounds / V. Prakash Reddy -- chapter 2 Optical Diagnostics for Characterizing Explosive Performance / Michael J. Hargather -- chapter 3 Solubility Thermodynamics of Organic Energetic Materials / Sanjoy K. Bhattacharia -- chapter 4 Mathematical Modeling and Experimental Investigations of Crystallization and Recrystallization Processes to Achieve Targeted Polymorphs and Crystal Size and Shape Distributions n * / Paul Redner -- chapter 5 Dynamic Characterization of Energetic Materials / Brahmananda Pramanik -- chapter 6 Sustainable High Explosives Development / Noah Lieb -- chapter 7 Printed Energetics -- The Path toward Additive Manufacturing of Munitions / Lori J. Groven -- chapter 8 Rheological Behavior of Energetic Gels and Suspensions n * / Bahadir Karuv -- chapter 9 Mixing, Coating, and Shaping n * / Jonghyun Park -- chapter 10 Continuous Processing and Shaping Using a Fully Intermeshing Co-Rotating Twin Screw Extruder n * / Moinuddin Malik -- part 2 The National Technology and Industrial Base of the Future -- chapter 11 Transition from Laboratory Innovation to Production and Military Fielding / Magdy Bichay -- chapter 12 Multidisciplinary Teams Required for the Development of Next-Generation Energetics / Kay J. Tindle -- chapter 13 The Nascent National Energetic Materials Initiative / Kay J. Tindle.
Keywords: Explosives; Chemical processes